Synthesis of M-Doped MoSe2 (M = Fe, Co, Ni) via Chemical Vapor Deposition for an Electrocatalytic Hydrogen Evolution Reaction - Xinya Chen; Xingchen Zhang; Jinying Zhang; Zhiyong Wang (Inorganics)
Given the high cost and limited availability of noble-metal-based catalysts in acidic media water electrolysis, developing cost-effective and high-performance non-noble metal catalysts is crucial for realizing large-scale hydrogen production. In this study, Fe-, Co-, and Ni-doped MoSe2 nanomaterials were synthesized via chemical vapor deposition, and their electrocatalytic performance for the hydrogen evolution reaction (HER) was systematically evaluated. Characterization techniques including X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy, scanning electron microscopy, and Raman spectroscopy were used to confirm the incorporation of doping elements and investigate their effects on the crystal structure and morphology of MoSe2. Electrochemical tests, including linear sweep voltammetry and cyclic voltammetry, revealed that the doping of Fe, Co, and Ni significantly enhanced the HER catalytic activity of MoSe2, with the Co-doped sample exhibiting the best performance, showing an overpotential of 0.293 V at 100 mA/cm−2 and a Tafel slope of 47 mV/dec. Furthermore, density functional theory calculations were employed to analyze the adsorption energy of hydrogen atoms on the catalysts, providing deeper insights into the role of doping in tuning the catalytic activity of MoSe2. This study offers new theoretical support and experimental evidence for the application of transition metal-doped MoSe2 in electrocatalysis.